learning loss LEARNING LOSS PEMBELAJARAN JARAK JAUH PENDIDIKAN PROFESI GURU DALAM JABATAN TAHUN 2023 - Edyan, Roly; Asrial; Kuswara, Ketut M.; Hikmah; Hadinata, Satrama Royal (Jurnal Lazuardi, 2024)
The purpose of this study is to describe distance learning and the difficulties faced by PPG participants in positions, lecturers and tutors that allow learning loss to occur. This research is a qualitative research with a descriptive approach. Data collection techniques used are observation, interviews and documentation. The results of this study found that the main form of learning loss found in students participating in PPG In Position was the form of learning loss that occurred when students felt ineffective in lectures compared to face-to-face in class. Most of the network constraints experienced by participants from the district and city areas in NTT will disrupt activities and the delivery of information received will not be optimal. PPG participants were still involved in teaching during PPG implementation. it was found next that it was difficult for the participants to understand and operate the internet and the material presented. Methods and solutions applied by PPG participants in their positions, tutor teachers and lecturers to improve concentration and effectiveness of learning properly include designing lessons/lectures well and varying according to the ability of PPG participants to access the internet. Pamomg teachers, lecturers and PPG participants communicate regularly about the obstacles encountered during online learning. The hybrid learning model is a combination of bold and alluring. Doing another approach model if PPG participants experience very limited internet communication